Draft Annual Plan 1981-82 Union Territory of Lakshadweep - Planning Commission (Planning Commission, 1981)
Lakshadweep, the smallest Uninn Territory of the Indian Union consist of 10 inhabited and 12 uninhabited islands and 5 islets lies scattered in the Arabian sea about 200-400Kms of the Kerala Coast. The.estimated population is 40,000 in 1980. the total area of the Union Territory is 32Sq.,Krjis. There are . no forest, Hills, Mountains, Lakes or Rivers in this Union Territory. All the islands are identical in structure and formation. There are shallow lagocns on the western i side encircled by coral reef, beyond which lies the deep sea.
Planning Department Secretariat Union Territory of Lakshadweep